KERAGAAN PERTUMBUHAN BIBIT KELAPA VARIETAS DxP LANGKAT PADA STRES KEKERINGAN DI PEMBIBITAN UTAMA - Wagino Wagino; Sri Murti Tarigan; Eka Bobby Febrianto (Jurnal Agro Estate, 2018)
This research was conducted on September 2017 – March 2018, in the greenhouse and laboratory of STIPAP Medan. This study used a factorial randomized block design with three repetitions, with total sample was 27 samples. Parameters observed were plant height, stem base diameter, leaf number, leaf area, root number, root length, root dry weight, shoot dry weight, root volume and number of stomata. The data obtained were analyzed statistically by analysis of variance (ANOVA) with Duncan's advanced test of 5%. The results showed that the di erence in the provision of water in the Main Nursery nursery a ected to the growth of oil palm seedlings significantly a ected plant height, canopy dry weight, leaf chlorophyll and root volume except stem diameter, leaf number, leaf area, number of roots, root length, weight dry root and number of stomata. Oil palm is a plant that has shallow roots (root fibers), so it is easy to experience drought stress. Water availability is one of the main limiting factors for the growth and production of oil palm plants. In the vegetative phase lack of water availability can cause damage to plant tissue, while in the generative phase can reduce the production of oil palm plants.